Children and Adolescents in Times of Crises in Europe - Grimm, Marc.; Ertugrul, Baris; Bauer, Ullrich; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents an analysis of the impact of the social crisis on the well-being of children and adolescents in Europe. Focusing on the fields of health, employment and social status, this book highlights that the impact of crisis has to be viewed in light of the state policies in reaction to crisis. Chapters in the book offer new perspectives of a reflexive crisis research objectifying crisis and analyzing what is referred to as crisis by whom, how, for what purposes and with which implicit or explicit solutions. This book offers empirical evidence and unique analytical approaches in the field of a child- and adolescent-oriented crisis research. .
Part 1. Introduction -- Chapter 1. Challenges and Tasks of a Child-oriented Crisis Research (Marc Grimm) -- Part 2. Impacts of Crises -- Chapter 2. Insecure Right from the Start? Socialization Effects of Self-perceived Job Insecurity (Christina Lübke) -- Chapter 3. Reviewing the Literature of Child Well-being in the Context of the Economic Crisis from a Non-monetary Perspective (Almudena Moren Mínguez) -- Chapter 4. On the Extremes: Poverty of Young Households in Greece and Germany (Brigitte Schels) -- Chapter 5. A Case Study of a Greek Family in Crisis (Nikos Panayotopoulos) -- Part 3. Policy Responses and Public Discourses on Crises -- Chapter 6. Transformation of Welfare Policy for Children and Adolescents in Post-crisis Austria (Roland Atzmüller) -- Chapter 7. The German Child Poverty Discourse and its Rhetorics of Crisis (Maksim Hübenthal) -- Chapter 8. The Discourse on Appropriate State Responses on the Impact of Economic Crisis on the Living Conditions of Children (Alexandra Kaasch).-Chapter 9. Policies of Crises in the EU Youth Field. How Political Discourses and Agendas Reshape the Concept of Youth (Andreas Heinen) -- Part 4. Subjective Processing of Crises -- Chapter 10. Immigrant Children in Switzerland During their Transition to Adulthood in Times of Crises: Lives Caught between Meritocratic Promise and Experiences of Inequality and Insecurity (Eva Mey) -- Chapter 11. Coping Strategies and Capabilities of Migrant Adolescents in Everyday Life Results of a Health-Ethnographic Project (Uwe H. Bittlingmayer) -- Chapter 12. "And then it got Really Hard". Innovative Approaches to Crises Research that Focus Individual Suffering in Times of Crisis (Franz Schultheis).
Keywords: Education; Children; Developmental psychology; Early childhood education; Sociology; Social groups; Childhood Education; Child and Adolescence Psychology; Early Childhood Education; Sociology of Family, Youth and Aging